A general model for trailing edge serrations simulation on wind turbine airfoils. Issue 4 (May 2021) - Cao, Huijing; Zhang, Mingming; Zhang, Yinan; Zhou, Teng
Highlights: A general modeling method for simulating effects of TESs is proposed. The geometrical characteristics and flow parameters of serrations are associated with added momentum sources. The modeled results demonstrate that proposed method is effective in replicating hydrodynamic and aeroacoustic characteristics as solid serrations. Abstract: Trailing edge serrations (TESs) are capable of noticeably suppressing the turbulent trailing edge noise induced by rotating wind turbine blades and become an integral part of a blade. However, the challenges involved in the dimensional design of serration height 2 h, wavelength λ and flap angle φ are yet to be dealt with in a satisfactory manner. To address the problem, a general model for simulating the effects of serrations on the hydrodynamic and aeroacoustic performance is proposed due to its ease of use and relatively low requirements for user input. The solid serrations are replicated by momentum sources calculated by its aerodynamic forces. Then, a case relevant to wind turbine airfoil is examined, a hybrid improved delay detached eddy simulation (IDDES) method coupled with FW-H integration is deployed to obtain the flow features and far-field sound pressure level. It is found that the modeling method could reproduce the flow field and noise as serrated airfoil.